The role of glacial cycles on the diversification and speciation of the birds of southern South America - Lijtmaer, Dario A (2023)
Fil: Lijtmaer Dario A. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia", CABA, Argentina